Digital reading platforms in literary learning: cultural understanding and engagement in Indonesian and Malay texts - Mohd Roslan Mohd Nor; Ahmad Zubaidi (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2026)
Background: The increasing use of digital reading platforms in humanities education has transformed how readers interact with texts, yet their impact on literary engagement, cultural understanding, and interpretive depth in Southeast Asian literary learning remains underexplored. Objective: This study investigates how digital reading platforms shape engagement, cultural meaning-making, and interpretive depth in the reading of Indonesian and Malay texts. Method: Employing a mixed-methods design, the study analyzes digitally mediated interactions—annotations, discussions, and reflective responses—across a curated corpus of canonical Indonesian and Malay works (published between the 1970s and 2010s) accessed through institutional digital reading platforms. Results: The findings reveal distinct patterns of digital engagement, with Indonesian texts eliciting stronger annotation-based interaction and Malay texts fostering more dialogic discussion. Cultural understanding emerges in differentiated forms, combining historical–political contextualization and ethical–communal interpretation. Furthermore, digital mediation supports advanced literary interpretation, including thematic synthesis, ideological critique, and intertextual reasoning. Implication: These results indicate that digital reading platforms function as cultural and interpretive mediation spaces rather than neutral technologies. Novelty: This study integrates literature-specific interpretive indicators with platform-based empirical data, offering a culturally grounded model of digital literary learning.